Eight out of every twenty-five married women have an unmet need for family planning in Meyu Muluke District, Eastern Ethiopia - Nuraddin Yigazu; Meleke Demene; Nega Assefa; Ibsa Mussa (Scientific Reports)
Abstract Unmet family planning needs are a critical public health problem in developing countries, particularly in Sub-Saharan Africa. An estimated 225 million women in developing countries who want to postpone, space, or avoid becoming pregnant do not use effective contraception methods, resulting in over 75 million unintended pregnancies each year, accounting for 84% of unintended pregnancies in developing countries. Thus, this study aimed to assess the determinants of the unmet need for family planning in Meyu Muluke District, Eastern Ethiopia. A community-based cross-sectional study was conducted from February 1 to 28, 2018, among 436 randomly selected currently married women of the reproductive age group in Meyu Muluke district, Eastern Ethiopia. Data were entered using Epidata version 3.1 and analyzed using Statistical Package for the Social Sciences (SPSS) version 25. Multivariate logistic regression was used to identify factors associated with the outcome variable, and a 95% confidence interval was used to declare statistical significance at a p-value of < 0.05. Overall, the magnitude of unmet need for family planning among currently married women was 36.02% (95% confidence interval (CI) 32.5–39.2%). Ages 25 to 29 years old [adjusted odds ratio (AOR) = 1.95, 95% CI (1.09–7.35), no formal education [AOR = 1.91, 95% CI (1.11–4.57)], middle wealth quintiles [AOR = 1.50, 95% CI (1.54–12.26)], some living children [0–1 and 2–3] [AOR = 1.47, 95% CI (1.33–8.83 [AOR = 0.67, 95% CI (1.26–18.80)], respectively], intending to use family planning in the future [AOR = 6.55, 95% CI (5.49–18.59)], and less than ten minutes to get to the family planning source [AOR = 2.33, 95% CI (1.15–4.72–2.92)] statistically significant to the unmet need for family planning. The study’s findings suggested that eight out of every twenty-five married women in Meyu Muluke District, Eastern Ethiopia, have unmet family planning needs. Age, education, children, intention, and time taken were significantly associated with the unmet need for family planning. Focusing on strategies that allow intervention in these factors is helpful to women because they, directly and indirectly, affect women’s health and educational achievement.